Ta-Based Catalyst Support for Proton Exchange Membrane Fuel Cell Applications. (14th September 2015) - Abhayawardhana, Anusha D.; Birss, Viola
Abstract : An ordered mesporous Colloid Imprinted Carbon with 80 nm sized pores (CIC80), a nitrided CIC80 (N-CIC80), and Ta oxynitride nanoparticles on nitrided CIC80 (TaOx Ny NPs/N-CIC80) were synthesized and evaluated as possible supports for Pt electrocatalysts in PEMFC applications. Transmission electron microscopy images showed that they have the expected pore size and that the TaOx Ny NPs are in the range of 5-20 nm in diameter. Potential stepping experiments revealed that the TaOx Ny NPs/N-CIC80 composite exhibits the highest corrosion resistance in 0.5 M H2 SO4, followed by N-CIC80 and then CIC80. Consistent with this, cyclic voltammetry revealed that the TaOx Ny NPs/N-CIC80 composite gave the smallest increase in surface area after the potential stepping experiment, followed by N-CIC80 and CIC80. These results suggest that a nitrided carbon surface is more corrosion resistant than carbon alone, and that the TaOx Ny NPs, which are themselves extremely stable, are conferring some of their stability to the carbon substrate.